Raising Students' Intercultural Competence Using Anecdotes about Gender - Nabiyevna, Rakhimova Yulduz (International Journal on Human-Computing Studies, 2023)
The article describes the role of anecdotes in raising students' intercultural competence. The didactic potential of anecdotes as an educational text is determined, which consists in the formation and development of cognitive activity, a positive effect on mental activity, an impact on the sphere of feelings and emotions, acquaintance with the language norm, development of a sense of language, enrichment of speech, in a hidden system for monitoring the correctness of understanding.